Quantitative analysis of male foetal DNA in maternal circulation in gestational diabetes mellitus, iron deficiency anaemia and hypertensive pregnancies - Zamanpoor, Mansour (2009)
Advances in molecular genetics have allowed the investigation of the foetal genome through analysis of circulating circulating DNA in maternal plasma. Cell free feotal DNA (fDNA) in maternal plasma or serum is widely investigated as a source of feotal genetic materials, both in studies of pregnancy related disorders and in planning strategies for non-invasive prenatal diagnosis. Increased amount of circulating fDNA in maternal plasma has been found in adverse pregnancies such as preeclampsia, foetal chromosomal aneuploidies, placental abnormalities, preterm labour and hyperemesis gravidarum. It was suggested that elevation of fDNA in maternal plasma could be used for early identification of adverse pregnancies. To date, no study has been done to investigate the fDNA in gestational diabetes mellitus (GDM) and anaemia, considered as the more common pregnancy related complications. The aim of this study was to quantify circulating fDNA levels in normal healthy pregnant women with the following clinical conditions: GDM, anaemia and hypertension (HTN). In this study, pregnant women carrying male singleton fetuses were recruited from the maternity Hospital Kuala Lumpur as study subjects. A total of a hundred and sixteen samples consisting of GDM (n=40), anameia (n=19), HTN (N=19), and normal pregnant women (N=38) carrying singleton male fetuses, were collected. The fDNA was extracted from maternal plasma. The fDNA concentrations were measured by quantitative real-time PCR amplification using TaqMan dual labeled probe system. The SRY gene which is located on Y chromosome was used as unique foetal marker. The mean fDNA concentrations for normal pregnancy samples was 41.14 GE/ml while the mean fDNA concentration for GDM pregnancy samples was 35.16 GE/ml, 30.96 GE/ml for anaemic pregnancy samples and 197.04 GE/ml for HTN pregnancy samples. No significant differences were observed in the mean fDNA concentration between normal and GDM pregnancy sample (P=0.627) and also between normal and anaemic pregnancy samples (P=0.535), but significant differences were observed between normal and HTN pregnancy samples (P=0.001). On the other hand, GDM and anaemia does not affect levels off DNA in maternal plasma while HTN significantly elevate the levels of fDNA in maternal plasma. Hence, there is a potential of using fDNA measurements as a predictive marker for the development of HTN, but if fDNA is used as an additional marker in prenatal screening test in the future, the findings of this study suggests that fDNA quantity will not be as informative for GDM and anaemic pregnancies as it is for HTN. In conclusion, measuring the overall amount of circulating fDNA maybe used as a general screening tool for pregnancy-associated disorders specifically hypertensive disorders, and it is hoped that further developments over the next few years will enable us to move even closer to use non-invasive nucleic acid-based prenatal diagnosis.